2020
DOI: 10.3390/microorganisms8111713
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Preliminary Indications of Divergent Niche Adaptation in Cryptic Clade II of Escherichia

Abstract: The evolution, habitat, and lifestyle of the cryptic clade II of Escherichia, which were first recovered at low frequency from non-human hosts and later from external environments, were poorly understood. Here, the genomes of selected strains were analyzed for preliminary indications of ecological differentiation within their population. We adopted the delta bitscore metrics to detect functional divergence of their orthologous genes and trained a random forest classifier to differentiate the genomes according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Almost all E. coli or Shigella genomes were within HierCC cluster HC2350_1, and genomes with other taxonomic or Clade designations belonged to other HC2350 clusters. However, soon after the definition of the EcoRPlus collection, additional genomes of Escherichia which were related to Clade II were described from inter-tidal marine and fresh water sediments near Hong Kong [61, 66]. Furthermore, due to its numerical predominance, E. coli overshadows other Escherichia species and sub-species within EcoRPlus.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all E. coli or Shigella genomes were within HierCC cluster HC2350_1, and genomes with other taxonomic or Clade designations belonged to other HC2350 clusters. However, soon after the definition of the EcoRPlus collection, additional genomes of Escherichia which were related to Clade II were described from inter-tidal marine and fresh water sediments near Hong Kong [61, 66]. Furthermore, due to its numerical predominance, E. coli overshadows other Escherichia species and sub-species within EcoRPlus.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all E. coli or Shigella genomes were within HierCC cluster HC2350_1, and genomes with other taxonomic or clade designations belonged to other HC2350 clusters. However, soon after the definition of the EcoRPlus collection, additional genomes of Escherichia which were related to clade II were described from inter-tidal marine and fresh-water sediments near Hong Kong [ 66 , 70 ]. Furthermore, due to its numerical predominance, E. coli overshadows other Escherichia species and subspecies within EcoRPlus .…”
Section: Resultsmentioning
confidence: 99%
“…R. Soc. B 377: 20210240 collection, additional genomes of Escherichia which were related to clade II were described from inter-tidal marine and fresh-water sediments near Hong Kong[66,70]. Furthermore, due to its numerical predominance, E. coli overshadows other Escherichia species and subspecies within EcoRPlus.…”
mentioning
confidence: 99%
“…While our isolates were from Hong Kong, China, the host-associated clade II strains originated from Australia, Gabon, and United States ( Walk et al, 2009 ; Clermont et al, 2011 ; Lescat et al, 2013 ; Walk, 2015 ; Gangiredla et al, 2018 ). We previously demonstrated that two groups of clade II genomes displayed signatures of functional divergence that were reflective of ecological differentiation to occupy gastrointestinal and external environments, respectively ( Shen et al, 2020 ). The study included genomes of isolates in this study.…”
Section: Discussionmentioning
confidence: 99%